The relationship between movement of the shank while running and foot alignment factors that lead to the onset of Achilles peritendinitis - Kurihara, Yasushi (J Phys Ther Sci, 2019)
[Purpose] To clarify the relationship between movement of the shank relative to the global reference frame (shank angle) while running, and foot alignment factors that lead to the onset of Achilles peritendinitis. [Participants and Methods] This study included 54 healthy male participants. Running at a constant speed was measured by three-dimensional motion analysis. The shank angle at the time of the first peak of vertical ground reaction force and maximum ankle dorsiflexion were analyzed. The magnitude of ankle plantarflexion, inversion, and adduction angle in the propulsive phase as well as static foot alignment (navicular index, and range of ankle dorsiflexion angle) were measured. The relationships between shank angle features and these parameters were investigated. [Results] Outward inclination of the shank occurred at the time of the first peak of vertical ground reaction force and maximum ankle dorsiflexion, with this increase in movement correlating with parameters that increased the risk of Achilles peritendinitis. [Conclusion] These findings suggest that evaluation of the shank angle on the frontal plane while running may be used to estimate the onset of Achilles peritendinitis in clinical practice.